IMPACT OF CADMIUM CHLORIDE ON ANTIOXIDANT SYSTEM IN THE LIVER OF RATS - Гутий, Б. В. (Scientific Progress & Innovations, 2013)
The features of the antioxidant system of rats with chronic cadmium toxicosiare disclosed. It wasThe features of the antioxidant system of rats with chronic cadmium toxicosiare disclosed. It wasresearched that cadmium chloride in toxic doses reduces enzyme activity of antioxidant system, asindicated by the decrease in enzyme glutathione peroxidase, hlutationreduktazy, superoxide dismutase,catalase and restored glutathione in the liver and blood of rats. The results indicate that chroniccadmium toxicosis leads to enhanced activation of lipid peroxidation.